The Family in Modern Society: A Legal and Social Analysis of Its Role, Challenges, and Protection in the United States - Mihoubi, Houria (Journal of Legal Studies and Researches, 2026)
The family has long been considered the most vital social institution in human civilization. Within the context of the United States, the family stands at the intersection of personal identity, moral education, and national stability. However, the twenty-first century has witnessed significant changes in the structure, function, and legal recognition of the family. This paper seeks to explore the definition and significance of the family as a foundational social and legal unit in American society, analyze the modern challenges confronting it, and evaluate the legal strategies adopted by the U.S. to preserve and strengthen familial bonds. Emphasis is placed on constitutional principles, statutory developments, family law reforms, and judicial interpretations that collectively shape the modern American family. The discussion combines a sociological perspective with a legal lens, demonstrating that the well-being of the family remains an indispensable condition for the stability of the Republic.